Vibrant punch needle décor : adorn your home with colorful florals and geometric patterns - Lowry, Melissa (Page Street Publishing Co., 2020)
"Melissa Lowry, author of Handmade Animal Dolls, shows readers how to embellish their home with the trending quick and easy art of punch needle embroidery. Readers can follow Melissa's gorgeous patterns and simple step-by-step instructions to create one-of-a-kind pieces. With just a punch needle-available at any craft store or online-yarn, and fabric readers can get started right away. Unlike traditional embroidery, knitting and crochet, there are no complicated stitches or special techniques. Slip the yarn into the needle and punch through the fabric to create a textured design. It's a relaxing, meditative craft, easy to do while chatting with friends or watching a favorite show. Inspired by Melissa's Mexican heritage, these patterns reflect the vibrant colors and geometric patterns of traditional textiles, with a modern touch. The book includes full-size templates, so readers can replicate Melissa's signature designs. Beginners can get that amazing handmade look in a just an hour or two, creating beautiful pillows, hoop art, napkins and placements from scratch. Readers who want to dive deeper into the craft can tackle large-scale rugs and wall-hangings along with more detailed designs. Contemporary, colorful, and truly unique, these projects make it easy to pick up a satisfying hobby and personalize your home"--